2024
DOI: 10.1002/advs.202306827
|View full text |Cite
|
Sign up to set email alerts
|

CSN6‐SPOP‐HMGCS1 Axis Promotes Hepatocellular Carcinoma Progression via YAP1 Activation

Kai Li,
Jiayu Zhang,
Haiwen Lyu
et al.

Abstract: Cholesterol metabolism has important roles in maintaining membrane integrity and countering the development of diseases such as obesity and cancers. Cancer cells sustain cholesterol biogenesis for their proliferation and microenvironment reprograming even when sterols are abundant. However, efficacy of targeting cholesterol metabolism for cancer treatment is always compromised. Here it is shown that CSN6 is elevated in HCC and is a positive regulator of hydroxymethylglutaryl‐CoA synthase 1 (HMGCS1) of mevalona… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 48 publications
0
2
0
Order By: Relevance
“…The study conducted by Tang et al demonstrated that contrary to its role in triggering proinflammatory signaling in the liver, obesity-induced cholesterol accumulation through mTORC1/SREBP2 signaling activation specifically inhibits NKT cell-mediated anti-tumor surveillance within the liver [ 126 ]. Recent research by Li et al demonstrated that signalosome 6 (CSN6) levels are elevated in HCC and act as an activator of hydroxymethylglutaryl-CoA synthase 1 (HMGCS1) in the mevalonate pathway, promoting the development of tumors [ 127 ]. The authors also illustrated that inhibiting CSN6 or HMGCS1 can potentially control the growth of liver cancer caused by MASLD.…”
Section: Metabolic Shifts and Reprogramming In Masld-induced Hccmentioning
confidence: 99%
“…The study conducted by Tang et al demonstrated that contrary to its role in triggering proinflammatory signaling in the liver, obesity-induced cholesterol accumulation through mTORC1/SREBP2 signaling activation specifically inhibits NKT cell-mediated anti-tumor surveillance within the liver [ 126 ]. Recent research by Li et al demonstrated that signalosome 6 (CSN6) levels are elevated in HCC and act as an activator of hydroxymethylglutaryl-CoA synthase 1 (HMGCS1) in the mevalonate pathway, promoting the development of tumors [ 127 ]. The authors also illustrated that inhibiting CSN6 or HMGCS1 can potentially control the growth of liver cancer caused by MASLD.…”
Section: Metabolic Shifts and Reprogramming In Masld-induced Hccmentioning
confidence: 99%
“…For example, synergistic activation of Myc/β-catenin, and YAP/TAZ boosts liver cancer cell proliferation and drug resistance (Bisso et al 2020 ). Among the specific upstream inputs in liver cancers, one study suggested that COP9 signalosome subunit 6 (CSN6), a member of the constitutive photomorphogenic 9 (COP9) protein complex implicated in tumorigenesis, drives YAP activation in HCC (Li et al 2024 ). In the diethylnitrosamine plus CCl 4 mouse model, CSN6 antagonizes speckle-type POZ protein (SPOP) and stabilizes hydroxymethylglutaryl-CoA synthase 1 (HMGCS1), resulting in YAP activation through the mevalonate pathway.…”
Section: Yap/taz Dysregulation In Liver Diseasesmentioning
confidence: 99%